Factors Associated with Prehospital Delay among Men and Women Newly Experiencing Acute Coronary Syndrome: A Qualitative Inquiry - Lourance A. Al Hadid; Marwa Al Barmawi; Nathira Abdelqader Ahmad Al Hmaimat; Noordeen Shoqirat (Cardiology Research and Practice)
Background. Delaying seeking health care for patients with acute coronary syndrome (ACS) causes high mortality and morbidity with variations among men and women regarding reasons for this delay. Objectives. This study explored factors associated with prehospital delay among men and women experiencing acute coronary syndrome for the first time in Jordan. Methods. 35 men and 33 women with ACS admitted and treated at the coronary and postcoronary care units. Results. Themes emerging from the data are knowledge about ACS, the resources related to health care, and concerns around family wellbeing. Owing to the traditional roles of men and women within the family, women felt responsible for maintaining the family, assisting in the financial conditions, and supporting family coherence by delaying hospitalization. Men were worried about the structural safety and maintenance of the family. Conclusion and Implications. Prehospital delay is common among first-timer ACS patients from both sexes, and thus, increasing awareness about ACS among the public from all age groups is necessary. Availability of specialized health care centers and equity in health care services are vital to improve public confidence in these health care settings and health outcomes.